2019
DOI: 10.1016/j.pneurobio.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

It’s all about tau

Abstract: Tau is a protein that is highly enriched in neurons and was originally defined by its ability to bind and stabilize microtubules. However, it is now becoming evident that the functions of tau extend beyond its ability to modulate microtubule dynamics. Tau plays a role in mediating axonal transport, synaptic structure and function, and neuronal signaling pathways. Although tau plays important physiological roles in neurons, its involvement in neurodegenerative diseases, and most prominently in the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
132
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 332 publications
(453 reference statements)
1
132
0
3
Order By: Relevance
“…1,40 PD is characterised by α-synuclein phosphorylation and fibrillization. 37,39 The hyperphosphorylation of Tau may promote its aggregation in vitro. 9 However, whether Tau phosphorylation occurs in the MPTP model of PD remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,40 PD is characterised by α-synuclein phosphorylation and fibrillization. 37,39 The hyperphosphorylation of Tau may promote its aggregation in vitro. 9 However, whether Tau phosphorylation occurs in the MPTP model of PD remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…41 The phosphor Tau (p-Tau) shows its tendency of aggregation which occurs in Alzheimer disease (AD), Pick disease and frontotemporal dementia with parkinsonism-17. 37 The phosphorylation of Tau reduces its affinity for microtubules and accumulation in the brain and causing related Tauopathies, 17 and also impact on microtubule binding and induces microtubule instability. 4 Although p-Tau links to the pathogenesis of AD and other Tauopathies, recent studies have revealed that p-Tau has a relationship with PD.…”
Section: Introductionmentioning
confidence: 99%
“…We will focus here on the disrupted inhibitory function of interneurons and consecutive hyperexcitability caused by Abeta -while we are aware of various other factors with potential roles for AD aetiology, such as vascular changes (19--21), neuroinflammation (22--25), genetics (26--28), environmental factors (29,30) and concomitant proteinopathies others than Abeta pathology (31,32). Beside Abeta there is a second molecular hallmark associated with the pathogenesis of AD: the phosphorylated Tau 'tubulin--associated unit' protein (8,33,34) which contributes to microtubule stability in the neural cytoskeleton (34). One major argument in favor of the more prominent involvement of Abeta in the pathogenesis of AD, in contrast to Tau, is its higher specificity to AD and its appearance in the early familial variants of AD, where the molecular pathway is better understood (14,18,35).…”
mentioning
confidence: 99%
“…Tau protein has multiple normal functions including the modulation of microtubule stability, axonal transport, modulation of signaling pathways, and adult neurogenesis [6]. Recent work has shown that toxicity is mediated by a gain of toxic function caused by tau that has become modified by conformational changes accompanied by oligomer formation and aggregation.…”
Section: Introductionmentioning
confidence: 99%